Pharmacogenetics, polypharmacy and drug interactions. The landscape of individualized medicine in dogs - Alfaro-Mora, Ramsés (2023)
Drug interactions, pharmacogenetics, and polypharmacy are three highly related areas of study that are involved in individualizing therapy across species. Variations in the response to drugs such as opioids, the presence of receptors and transporters associated with polymorphic genes, as well as pharmacokinetic changes resulting from differences in phase I and phase II metabolism, lead to the existence of a multiplicity of factors that can affect response to drugs. In addition, the joint administration of different active ingredients (polypharmacy) is related to a greater number of drug interactions, which, associated with the pharmacogenetic conditions of the different breeds of dogs, make personalized medicine a very broad field in which veterinary medicine is still taking its first steps. The present work seeks to analyse the current state of knowledge about the variation of the response to drugs in the canine species, considering drug interactions as a consequence of polypharmacy, and how pharmacogenetics assumes an important role to understand these phenomena. in the different breeds.